THEORETICAL CONCEPT OF THE ROLE OF HUMAN CAPITAL IN SHAPING COMPETITIVENESS - Majidov , Qobiljon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis provides a comprehensive theoretical analysis of the role of human capital in shaping competitiveness. The historical development of the human capital concept, its fundamental theoretical foundations, and the mechanisms of its influence on competitiveness at individual, enterprise, and national levels are examined in detail. In the context of the modern economy, the role of knowledge, skills, health, and motivation as key factors of competitiveness is substantiated both theoretically and empirically. Investment in human capital is emphasized as a critical driver of economic growth, innovation, and sustainable development. The practical significance and prospects of this theory in the context of Uzbekistan are also discussed. The article is written at the intersection of economic theory, labor economics, and competitiveness theories, meeting the requirements of high-level Scopus-indexed journals through its scholarly style and in-depth analysis.